Oral symptoms and systemic condition associeted with the quality of life of patients with Neuromusculars diseases (Research, Society and Development, 2022)
This study aimed to evaluate the impact of oral symptoms and systemic conditions on oral health-related quality of life (OHRQOL) in patients with neuromuscular diseases (NMD). An observational and cross-sectional study was carried out with a convenience sample of patients with NMD at the Neurorehabilitation Outpatient Clinic of a University Hospital. Data included information about patients' sociodemographic characteristics, underlying disease, comorbidities and medications, and oral symptoms such as oral burning, dysgeusia, dysphagia and sialorrhea. The index of Decayed, Missing, and Filled Teeth (DMFT) was also applied. The Oral Health Impact Profile (OHIP-14) questionnaire was used to evaluate the OHRQoL. The collected data were submitted to statistical analysis using the chi-square test, considering significant values of p